Experimental Research on the Impact of Interface Temperature on the Adhesion Properties of Clay under the Condition of Different Contacting Time - Tao Qiu; Yonggang Zhang (Geofluids)
Mud cakes are very likely to occur at the shield cutter when the shield machine passes through a clay stratum, which adhere to the cutter and reduce the excavation efficiency. Due to the thrust of the cutter, the mud cakes are compacted and cause friction at the soil-structure interface, which results in high temperature and aggravates the adhesion, and the effect tends to become stronger as the heating process lasts. In this paper, the effects of the interface temperature and the contacting time between the soil and the hot surface on the adhesion properties of the soil were studied by a self-made adhesion test device. According to the findings, at low interfacial temperature (≤40°C), both the adhesion force and the amount of adhered soil were insignificant in a short term, and the effects were found to be strengthened as the contacting time went on; at the high interfacial temperature (≥50°C), very significant soil adhesion occurred at the structure surface within a short time, and as the contacting time increased, the amount of the adhered soil decreased rapidly while the adhesion force kept increasing, and both tended to remain a constant and become independent with the temperature after a long-term contact. This study is of guiding significance for understanding the formation and development of the shield mud cakes during shield construction.